PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN LINGKUNGAN KERJA TERHADAP KINERJA GURU SEKOLAH DASAR NEGERI DI KECAMATAN BLORA KABUPATEN BLORA - Hermin Nugraheni; Endang Wuryandini; Yovitha Yuliejantiningsih (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The background to this research is the low performance of state elementary school teachers in Blora sub-district, Blora Regency. The problem of low teacher performance is caused by several factors including transformational leadership style and the work environment. This research aims to determine the magnitude of the influence of transformational leadership style and the work environment on the performance of State Elementary School teachers in Blora District, Blora Regency. This type of research is quantitative research with an ex post facto approach. The population in this study were all state elementary school teachers in Blora District, Blora Regency, consisting of 386 teachers from 52 elementary schools. After formulating it using Slovin, a sample of 196 respondents was obtained. The data collection technique used was by giving questionnaires to respondents. Research results: (1) There is an influence of transformational leadership style on the performance of state elementary school teachers in Blora District, Blora Regency, which is expressed by the equation Y = 52.317 + 0.416X1. (2) There is an influence of the work environment on the performance of state elementary school teachers in Blora District, Blora Regency, which is expressed by the equation Y = 37.137 + 0.567X2. (3) There is an influence of transformational leadership style and work environment on the performance of state elementary school teachers in Blora District, Blora Regency, which is expressed by the equation Y = 23.057 + 0.233X1 + 0.483X2.